PEMILIHAN PRODI AKUNTANSI DAN FAKTOR YANG MEMPENGARUHI PADA MAHASISWA BARU PRODI AKUNTANSI PERGURUAN TINGGI â€œXâ€ - Minarso, Bambang; Machmuddah, Zaky (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
At present the global issues regarding the industrial era 4.0 greatly impact the development of technology so that it has an impact on the decrease in the number of new students of several study programs in all tertiary institutions in Indonesia. The purpose of this study is to find out what factors make the admission of new accounting students in Higher Education X fluctuate, so that the results of this study can be useful to improve the strategy of new student admissions in Higher Education X's accounting study programs. The population in this study is all students of accounting studies in Higher Education X. The sample used in this study was taken using accidental sampling technique from new students of accounting study programs, obtained 199 respondents. Multiple linear regression is used as a data processing tool. The results of multiple linear regression indicate that psychological factors influence the decision to choose a study program, while social and cultural factors do not influence the decision to choose a study program. This shows that the most appropriate marketing strategy for prospective accounting study program students is by instilling a mindset that the accounting study program and the accounting profession are still needed by the industrial world and government agencies.